2001
DOI: 10.1200/jco.2001.19.22.4195
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Multicenter Phase II Study Comparing a Combination of Fluorouracil and Folinic Acid and Alternating Irinotecan and Oxaliplatin With Oxaliplatin and Irinotecan in Fluorouracil-Pretreated Metastatic Colorectal Cancer Patients

Abstract: The every-3-weeks OC combination is safe and active in advanced 5-FU-resistant CRC patients. The lower activity data seen with the tritherapy regimen may be related to the lower dose intensities of irinotecan and oxaliplatin in this schedule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 29 publications
2
28
0
Order By: Relevance
“…Phase I three-drug clinical trials [19,20,21] have already demonstrated nonoverlapping dose-limiting toxicities and safety profiles. Phase II studies [16,17,18, 22, 23] which investigated different three-drug regimens reported interesting data on activity (response rate ranged from 32 to 69.2%, time to tumor progression from 8.2 to 14 months). Falcone et al [22] achieved noteworthy results, with response rate 71.4%, median time to tumor progression 10.4 months and median overall survival 26.5 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phase I three-drug clinical trials [19,20,21] have already demonstrated nonoverlapping dose-limiting toxicities and safety profiles. Phase II studies [16,17,18, 22, 23] which investigated different three-drug regimens reported interesting data on activity (response rate ranged from 32 to 69.2%, time to tumor progression from 8.2 to 14 months). Falcone et al [22] achieved noteworthy results, with response rate 71.4%, median time to tumor progression 10.4 months and median overall survival 26.5 months.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical settings, phase I and II studies have already shown the feasibility and activity of the three-drug combination in both chemo-naïve and pretreated MCC patients [16,17,18,19,20,21,22,23, 27]. …”
Section: Introductionmentioning
confidence: 99%
“…It seems that even combined with IRI, TAS-102 could not suppress tumor growth, compared with combination chemotherapies with 5-FU plus OX or 5-FU plus IRI. Second-line chemotherapy generally needs a much higher PFS, for example, that of 5-FU plus OX or 5-FU plus IRI was 8.2 months [6]. In our case, TAS-102 alone could shrink the size of 5-FU-resistant liver metastasis to approximately 60%, and its PFS reached to over 12.5 months without severe toxicities.…”
Section: Discussionmentioning
confidence: 67%
“…Inter-individual differences in the pharmacokinetics of its active metabolite, SN-38, cause the variations in the effect of the drug (6). Several studies in relation with different doses and schedules of CPT-11 alone or in combination with other agents are ongoing to investigate its use as first or secondline therapy (7,8), with a view to optimising the therapeutic outcome for these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Inter-individual differences in the pharmacokinetics of its active metabolite, SN-38, cause the variations in the effect of the drug (6). Several studies in relation with different doses and schedules of CPT-11 alone or in combination with other agents are ongoing to investigate its use as first or secondline therapy (7,8), with a view to optimising the therapeutic outcome for these patients.On the other hand, Glutathione S-transferases (GSTs) are considered an important family of detoxifying enzymes for mutagens. They protect cellular macromolecules from damage by catalysing the conjugation of toxic and carcinogenic electrophilic molecules with glutathione.…”
mentioning
confidence: 99%